Intensive exercise ameliorates motor and cognitive symptoms in experimental Parkinson’s disease restoring striatal synaptic plasticity - Marino, Gioia; Campanelli, Federica; Natale, Giuseppina; De Carluccio, Maria; Servillo, Federica; Ferrari, Elena; Gardoni, Fabrizio; Caristo, Maria Emiliana; Picconi, Barbara; Cardinale, Antonella; Loffredo, Vittorio; Crupi, Francesco; et al. (Science advances, 2023)
Intensive physical activity improves motor functions in patients with Parkinson’s disease (PD) at early stages. However, the mechanisms underlying the beneficial effects of exercise on PD-associated neuronal alterations have not been fully clarified yet. Here, we tested the hypothesis that an intensive treadmill training program rescues alterations in striatal plasticity and early motor and cognitive deficits in rats receiving an intrastriatal injection of alpha-synuclein (α-syn) preformed fibrils. Improved motor control and visuospatial learning in active animals were associated with a recovery of dendritic spine density alterations and a lasting rescue of a physiological corticostriatal long-term potentiation (LTP). Pharmacological analyses of LTP show that modulations of N -methyl- d -aspartate receptors bearing GluN2B subunits and tropomyosin receptor kinase B, the main brain-derived neurotrophic factor receptor, are involved in these beneficial effects. We demonstrate that intensive exercise training has effects on the early plastic alterations induced by α-syn aggregates and reduces the spread of toxic α-syn species to other vulnerable brain areas. Intensive exercise reshapes functional and structural aspects of corticostriatal synapses in an α-syn-based animal model of PD.